Political Marketing Towards the 2024 Local Elections in the Frame of Digital Democracy - Bayu Priambodo (Master Program of Sociology, Universitas Malikussaleh,, 2023)
The development of technology and information has changed human life towards digital transformation, including in the political sphere. Currently, the world of politics has shifted to the digital world. The political shift towards digitalization gave rise to the concept of digital democracy. This research will focus on political marketing in digital democracy, considering that Indonesia will hold simultaneous elections in 2024. The research method used in this study is qualitative and is analyzed using the concept of digital democracy. The results of this study indicate that political marketing will be more crowded in the digital world because most people prefer to find information online. After all, it is considered faster and easier. However, you must also be vigilant about hoax news in the digital world. Currently more than 50% of Indonesian people access information using the internet, so that the pattern of political marketing has also shifted to the digital world, this shift has experienced a shift in political narratives related to religion, ethnicity and race.